2013
DOI: 10.1080/09640568.2012.709180
|View full text |Cite
|
Sign up to set email alerts
|

Household waste recycling: national survey evidence from Italy

Abstract: The paper analyses the determinants of household recycling in Italy with particular emphasis on and household income playing the biggest role. Our findings also show that the presence of recycling bins for waste improves household recycling behaviour for all materials whereas difficulty to reach recycling bins adversely affects household recycling outcomes. Household judgments on waste disposal charges have no effect on the recycling effort. As expected, residency in Southern Italy is associated with the lowes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
49
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 46 publications
(33 reference statements)
8
49
0
2
Order By: Relevance
“…This includes recycling (Callan and Thomas, 2006;Ferrara and Missios, 2005;Fiorillo, 2013;Hage et al, 2009;López-Mosquera et al, 2015;Zen et al, 2014), energy conserving practices (Mills and Schleich, 2012), water saving behaviours (Clark and Finley, 2007) and a wide range of carbon emission reduction actions e.g. reducing the use of car, avoiding taking short-haul flights, reducing the consumption of disposable items and buying seasonal and local products (Ortega-Egea et al, 2014).…”
Section: Education and Environmental Behaviourmentioning
confidence: 99%
“…This includes recycling (Callan and Thomas, 2006;Ferrara and Missios, 2005;Fiorillo, 2013;Hage et al, 2009;López-Mosquera et al, 2015;Zen et al, 2014), energy conserving practices (Mills and Schleich, 2012), water saving behaviours (Clark and Finley, 2007) and a wide range of carbon emission reduction actions e.g. reducing the use of car, avoiding taking short-haul flights, reducing the consumption of disposable items and buying seasonal and local products (Ortega-Egea et al, 2014).…”
Section: Education and Environmental Behaviourmentioning
confidence: 99%
“…As noticed Klein and Huffman (2013) although "recycling is one of the lower-impact environmental sustainability behaviors, it still provides substantial savings to organizations " (p. 8). Surprisingly, whereas most prior research has addressed individuals' recycling behavior in non-work domains (e.g., Fiorillo , 2013;Hornik, Cherian, Madansky & Narayana, 1995;Gillespie & Bennett, 2013;Schultz, Oskamp & Mainieri, 1995;Sidique, Lupi & Joshi, 2010;Tucker & Speirs, 2003), workplace recycling remains largely overlooked, with the exception of a handle of research (Austin, Hatfield, Grindle, & Bailey, 1993;Brothers, Krantz & McClannahan, 1994;Greaves, Zibarras & Stride, 2013;Lee, De Young & Marans, 1995;MacDonald, 2011;Price & Pitt, 2012;Tudor, Barr, Gilg, 2007). Typically, these prior investigations on recycling in organizational settings have to a large extent put the emphasis on facilities, and revealed that maintaining employee willingness to use appropriate bins is an important challenge for organizations (Austin et al, Ramus (2001) has found that employees are more likely to engage in environmental initiatives on the job when they perceive that their supervisor encourages new ideas, is open-minded, provides regular training to subordinates, shares critical information, rewards efforts, and shows a sense of responsibility.…”
Section: Introductionmentioning
confidence: 97%
“…In fact, if local inhabitants have more environmental knowledge and awareness levels on sustainable waste management practices, they are more likely to engage in pro-environmental behaviours [19,46]. Furthermore, in a national survey conducted in Italy, it was demonstrated that, if households are conveniently provided with recycling bins, they are more likely to participate in recycling programmes for all materials [47]. During a study investigating capacity building in rural Guatemala, it was shown that one of the barriers hampering the widespread adoption of sustainable waste management schemes is the long distances traversed by recyclers and the high costs of transporting small volumes of recyclable material to buy-back centres [17].…”
Section: Aspects Of Municipal Waste Management and Recycling At Commumentioning
confidence: 99%
“…During a study investigating capacity building in rural Guatemala, it was shown that one of the barriers hampering the widespread adoption of sustainable waste management schemes is the long distances traversed by recyclers and the high costs of transporting small volumes of recyclable material to buy-back centres [17]. This means that recycling, as a sustainable waste management option, will be practised more efficiently only if a closer recycling facility is built around communities in need of such infrastructure [17,47,48].…”
Section: Aspects Of Municipal Waste Management and Recycling At Commumentioning
confidence: 99%